The Relationship between Nutritional Behavior and Dietary Patterns and the Incidence of Chronic Energy Deficiency in Pregnant Women in the Work Area of Sendana II Health Center in 2025 - Nur Anisafauziah Ilham; Sri Aryati Artha; Al Munawarah Fattah; Agusliani Agusliani (International Journal Of Health Science, 2026)
Background: Chronic energy deficiency (CED) is one of the nutritional problems often faced by pregnant women, especially in developing countries. CED can have serious impacts on maternal and fetal health, including the risk of complications during pregnancy, premature birth and stunted fetal growth. CED is a condition where a person suffers from chronic food shortages characterized by an upper arm circumference (MUAC) <23.5 cm, resulting in health problems. Objective: To determine the relationship between nutritional behavior and dietary patterns with the incidence of chronic energy deficiency (CED) in pregnant women in the working area of Sendana II Health Center in 2025. Method: The type of research used in this study is a cross-sectional study, and uses the Slovin formula to determine the minimum sample size. Results: Based on the Chi-square analysis , it shows that nutritional behavior and eating patterns each show a value of p = 0.002 (p <0.05) and p = 0.000 (p <0.005), meaning that there is a relationship between nutritional behavior and eating patterns and the incidence of chronic energy deficiency (CED) in pregnant women at the Sendana II Community Health Center in 2025. Conclusion: There is a significant relationship between nutritional behavior and eating patterns and the incidence of chronic energy deficiency (CED) in the work area of the Sendana II Community Health Center in 2025 .